Whole-cell (+)-ambrein production in the yeast Pichia pastoris - Moser, Sandra; Strohmeier, Gernot A.; Leitner, Erich; Plocek, Thomas J.; Vanhessche, Koenraad; Pichler, Harald (Metabolic engineering communications, 2018)
The triterpenoid (+)-ambrein is a natural precursor for (-)-ambrox, which constitutes one of the most sought-after fragrances and fixatives for the perfume industry. (+)-Ambrein is a major component of ambergris, an intestinal excretion of sperm whales that is found only serendipitously. Thus, the demand for (-)-ambrox is currently mainly met by chemical synthesis. A recent study described for the first time the applicability of an enzyme cascade consisting of two terpene cyclases, namely squalene-hopene cyclase from Alicyclobacillus acidocaldarius (AaSHC D377C) and tetraprenyl-β-curcumene cyclase from Bacillus megaterium (BmeTC) for in vitro (+)-ambrein production starting from squalene. Yeasts, such as Pichia pastoris, are natural producers of squalene and have already been shown in the past to be excellent hosts for the biosynthesis of hydrophobic compounds such as terpenoids. By targeting a central enzyme in the sterol biosynthesis pathway, squalene epoxidase Erg1, intracellular squalene levels in P. pastoris could be strongly enhanced. Heterologous expression of AaSHC D377C and BmeTC and, particularly, development of suitable methods to analyze all products of the engineered strain provided conclusive evidence of whole-cell (+)-ambrein production. Engineering of BmeTC led to a remarkable one-enzyme system that was by far superior to the cascade, thereby increasing (+)-ambrein levels approximately 7-fold in shake flask cultivation. Finally, upscaling to 5 L bioreactor yielded more than 100 mg L−1 of (+)-ambrein, demonstrating that metabolically engineered yeast P. pastoris represents a valuable, whole-cell system for high-level production of (+)-ambrein. [Display omitted] •Squalene accumulation in P. pastoris for triterpenoid biosynthesis.•First whole-cell biosynthesis of (+)-ambrein in yeast.•Cell and enzyme engineering improved (+)-ambrein yield to> 100 mg L−1 culture.